Industry 4.0 as a facilitator for the inclusion of PwDs: a conceptual proposal (Research, Society and Development, 2024)
Although access to the market for people with special needs (PwDs) is guaranteed by law, through the process of inclusion and quotas, large gaps are observed between what is recommended by legislation, what would be the theory and the practical reality involving the process of inclusion of people with disabilities in the job market. The present work aims to value the culture of the presence of people with disabilities in the job market in order to confirm the importance of implementing a continuous learning process within companies and provide an integration process that can be relevant so that everyone can have opportunities to stand out in the market in which it operates, regardless of its physical, motor and intellectual needs where providing inclusion becomes the responsibility not only of governments, companies, but also of society as a whole where the existing processes in industry 4.0 can be this facilitator. The methodologies used were descriptive and bibliographical research, in order to develop a concept to allow for a better inclusion process involving society and organizations.